Main Reform on Higher Education Systems in Korea - Jeong-Kyu Lee (Revista Electrónica de Investigación Educativa)
This article examines the main reform in current Korean higher education by briefly reviewing a historical perspective on higher education reform, then discussing the main issues of recent education reform since 1994 by focusing on legal and administrative system changes, reforms or innovations of university management, and reforms of organizational culture. Finally, the main challenges and visions of Korean higher education systems toward the 21 st century are presented.